Dynamic Impurity Redistributions in Kesterite Absorbers. Issue 6 (12th June 2020) - Grini, Sigbjørn; Aboulfadl, Hisham; Ross, Nils; Persson, Clas; Platzer-Björkman, Charlotte; Thuvander, Mattias; Vines, Lasse
Abstract : Air annealing and heavy‐water treatment of kesterite solar‐cell absorbers lead to a redistribution of impurities affecting the power conversion efficiency. Sigbjørn Grini and co‐workers (see article number 2000062 ) have performed atom probe tomography analysis of Cu2 ZnSnS4 absorbers, revealing the elemental distribution at nanometer scale in three dimensions. On the cover, Cu and Na atoms are shown (Cu atoms are displayed only within one half of the reconstruction to better visualize the dispersion of Na atoms). A two‐dimensional concentration map positioned in the middle of the reconstruction shows the Cu inhomogeneity within the grain interior. Na‐decorated dislocations are marked by "1D" and Na‐rich clusters by "C". A planar defect, located top left, exhibits Na segregations at the defect and Cu enrichment nearby.